Optimizing the Components of Active Water Fracturing Fluids for Coalbed Methane Using Biochemical Engineering Approaches - Zhang, Hong (International Journal of Natural Resources and Environmental Studies, 2025)
Hydraulic fracturing is an effective technique for enhancing coal seam permeability. While coal as a macromolecular organic material, can be biodegraded by microorganisms, limited research has explored the integration of these processes to develop bioactive fracturing fluids. This study employed Shengli lignite from Inner Mongolia as the substrate and coal seam mine water as the microbial inoculum. Through single-factor experiments and orthogonal experimental design, investigated the effects of wetting agent concentration, clay stabilizer concentration, and demulsifier concentration in bioactive fracturing fluid additives on the microbial methanogenesis of lignite. The results indicate that, in terms of their impact on gas production, the three factors rank in descending order of significance as follows: wetting agent concentration, clay stabilizer concentration, and demulsifier concentration. Orthogonal analysis identified the optimal additive combination for bioactive fracturing fluid as 0.15% wetting agent, 2% clay stabilizer, and 0.15% demulsifier by mass concentration. The optimized formulation led to a substantial 31.73% increase in biogas yield compared to the pre-optimized condition. Three-dimensional fluorescence spectroscopy revealed that the fluorescence intensity of fulvic acid-like and humic acid-like substances was higher after optimization, indicating more complete degradation of the coal samples. Furthermore, metagenomic sequencing analysis demonstrated that the optimized bioactive fracturing fluid significantly improved the microbial community structure, markedly increasing the abundance of Methanosarcina. The predominant methane metabolism pathways were acetate fermentation and carbon dioxide reduction, with a substantial increase in the gene abundance related to methanogenic pathways, thereby promoting microbial methane production. These findings elucidate the mechanistic effects of bioactive fracturing fluid composition on lignite biogasification and provid.